Debates and Reforms to the Police in Chile, Colombia and Ecuador: A Comparative Study (Palimpsesto, 2021)
Chile, Colombia and Ecuador have experienced attempts of police reform in response to the need to generate change within these institutions. This research aims to identify the events that led to police reform processes in the three cases, generating a comparison between the processes and debates around police reforms, emphasizing common actors and socio-political processes to establish convergences and differences in the reform processes. As well as contributing to a debate on police institutionality and the paradigms from which citizen security and public order are discussed, especially as a result of the human rights violations committed by the police in these countries.
Keywords: Police; Latin America; Modernization; Reform; Human Rights violations